Depression and anxiety during pregnancy and the postpartum period in women with epilepsy: A review of frequency, risks and recommendations for treatment. (May 2015) - H. Bjørk, Marte; Veiby, Gyri; A. Engelsen, Bernt; Gilhus, Nils Erik
Highlights: Peripartum depression affects 16–35% of women with epilepsy. Risks include frequent seizures, polytherapy, previous psychiatric disease and sexual/physical abuse. Screen for depression, anxiety and risk factors before, during and after pregnancy. Use non-pharmacological antidepressive treatment during pregnancy and breastfeeding. Measure serum-concentrations of antiepileptic and antidepressive drugs. Abstract: Purpose: To review available data and provide treatment recommendations concerning peripartum depression, anxiety and fear of birth in women with epilepsy (WWE). Method: The PubMed, the LactMed, the DART and the Cochrane database were searched for original articles concerning psychiatric disease in the peripartum period in WWE. Results: Point prevalence of depression from 2nd trimester to 6 months postpartum ranged from 16 to 35% in women with epilepsy compared to 9–12% in controls. The highest estimates were found early in pregnancy and in the perinatal period. Anxiety symptoms 6 months postpartum were reported by 10 and 5%, respectively. Fear of birth symptoms were increased in primiparous WWE compared to controls. Previous psychiatric disease, sexual/physical abuse, antiepileptic drug (AED) polytherapy, and high seizure frequency emerged as strong risk factors. Depressed WWE rarely used antidepressive medication during pregnancy. No evidence was available concerning treatment effects or impact on the developing child. Conclusion: Peripartum depression is frequent in WWE and seldom medically treated. Health personnel should screen WWE for psychiatric disease and risk factors during pre-pregnancy planning, pregnancy and postpartum follow up. Treatment decisions should rely on efficacy and safety data in peripartum patients without epilepsy and non-pregnant people with epilepsy. Consequences of in utero exposure to AED therapy in combination with antidepressants are not known, and non-pharmacological treatment should be tried first.